Bleomycin‐induced flagellate hyperpigmentation. Issue 4 (24th February 2017) - Larson, Krista N.; Gagnon, Amy L.; Wilson, Barbara B.
Key Clinical Message: A 27‐year old male with Hodgkin's lymphoma was treated with combined chemotherapy that included bleomycin. He presented with pruritic erythematous, edematous linear lesions and was diagnosed to have flagellate hyperpigmentation, a rare side effect of bleomycin chemotherapy. Abstract : A 27‐year old male with Hodgkin's lymphoma was treated with combined chemotherapy that included bleomycin. He presented with pruritic erythematous, edematous linear lesions and was diagnosed to have flagellate hyperpigmentation, a rare side effect of bleomycin chemotherapy.